Random sampling applied to the measurement of a DC signal immersed in noise - Carrica, Daniel Oscar (2001)
This paper introduces the use of random sampling for the recovery of DC signals immersed in noise. This technique avoids the use of antialiasing filters even if the disturbance frequencies are higher than the maximum sampling frequency available. The use of random sampling and a moving average filter for the measurement of DC signals is mathematically and experimentally demonstrated.